“A sick man’s dream”: Jephthah, Judges, and Blake’s Visions of the Daughters of Albion - Crafton, Lisa (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractEven a cursory reading of the eleventh chapter of Judges suggests obvious parallels between the Jephthah story and Blake’s Visions of the Daughters of Albion; however, Blake’s six illustrations of Judges (including two of Jephthah and his daughter) irrefutably document his appropriation of the story. No critic has connected the Jephthah story of virgin sacrifice to Oothoon’s fate, nor have Blake’s illustrations of the Judges narrative received much attention. My argument is that Blake’s contrary reading of the book of Judges should inform our critical reading of Visions. This intertextual analysis emphasizes the poem’s representation of the female body as a site of sacrifice and how both Blake’s illustrations and the poem position readers for this spectacle of virginity and violence. Reading Blake’s illustrations of the Jephthah narrative—visual revelations of issues of sexual power—amplifies the poem’s cultural power, its iconic representation of a patriarchal obsession with virginity, demonstrable in late eighteenth-century British culture but with ties to biblical, Hebraic representations of virginity and violence. Blake’s culturally-targeted revision of Jephthah’s daughter defies eighteenth-century British cultural strictures about female purity and marital customs by transforming the daughter virgin’s lament at not being able to marry into Oothoon’s redefinition of sexual purity. Further, my reading refutes the widespread critical opinion that in the ending of the poem, the heroine Oothoon offers free love that is, in Mellor’s words, a “male fantasy,” serving the interests of the “male libertine, ”and underscores the poem’s critique of mandated female virginity and culturally-endorsed violence. Finally, Finally, the illustrations and the poem document Blake’s engagement with this biblical book where Israel’s destiny unfolds through accounts of judges who again and again misjudge, who enact sexual violence and fail to see its connection with their own violent ends. Blake’s Visions begins and ends with a chorus of daughters—in between it chronicles the horrors of exploitation, rape, slavery, cultural imperialism and links those to individual sexual repression, like Theotormon’s troubled image of Oothoon, like Jephthah’s sacrifice of his daughter, truly a “sick man’s dream.”